Glacial lake outburst caused by small amplitude wave overflow. Issue 1 (January 2021) - Wang, Baoliang; Wang, Hongfei; Yao, Zhenguo
Abstract: In this study, a series of glacial lake dam overflow experiments are conducted. In those experiments, the influence of surge scale on dam outburst was studied. According to the results of the experiment, the surge overflow is the direct trigger factor of the natural lake outburst, and the periodic return of the small amplitude surge is favorable to the formation of the dam outburst. The scale of the surge will affect the time required to form the break, and the shape of the outburst flood curve. The scour movement of the water in the dam back side will make the dam form a gully. The scour movement of the water in the back side will make the dam form a gully, when the gully developed to a certain extent, the interaction between the water flow and the bottom bed changed from shear action (friction resistance) to impact action, which greatly increased the erosion and destruction capacity of the water flow and formed a "headcut". The water flow constantly brushes the bottom of the "headcut" and produced retrospective erosion, make the break constantly expanded, eventually result in dam break.